Novel Multiple Endpoint Approaches for Assessing Genotoxicity and Carcinogenicity Potential In Vitro - Linda Reilly (2024)
The current limitations of in vitro genotoxicity testing, often resulting in misleading predictions of in vivo carcinogenic potential, prompted a project aimed at enhancing predictive accuracy. This study integrated traditional genotoxicity data with a multi-endpoint approach, encompassing various cellular endpoints relevant to carcinogenicity. The developed multi-endpoint testing platform was compared with an innovative Multi-Endpoint Genotoxicity Assessment (MEGA) screen, an automated imaging-based micronucleus assay in A549 cells, providing insights into genotoxic mechanisms. The Swansea-based multi-endpoint platform conducted assays, including cytotoxicity, micronuclei induction (Mn), cell cycle perturbations, and other cancer-related endpoints over time in TK6 and A549 cells. A group of compounds (Cisplatin, Temozolomide, Trichostatin A, Potassium Bromate) underwent assessment across both cell lines. Examining Cisplatin as an example, the multi-endpoint strategy revealed a significant increase in Mn at 4 µM (*P ≤ 0.05), 50% cytotoxicity at 6 µM, early (*P ≤ 0.05) and late-stage (**P ≤ 0.01) apoptosis at 6 µM, and G2/M arrest (****P ≤ 0.0001) at 4 µM after 24 hours with a 24-hour recovery in TK6 cells. In A549 cells, the same time point exhibited a significant Mn increase at 0.5µM (*P ≤ 0.05), 50% cytotoxicity at 3 µM, early-stage apoptosis (*P ≤ 0.05) at 3 µM, and an increase in G1 population (*P ≤ 0.05) starting at 0.5µM. In the MEGA screen, A549 cells demonstrated responses at substantially higher doses (1000 µM), accompanied by significant toxicity. A multiple endpoint approach provided a comprehensive understanding of cisplatin's mechanism of action. Concurrent evaluation of both multi-endpoint systems identified strengths and weaknesses, facilitating the development and refinement of a predictive testing platform for in vitro carcinogenicity assessment. Future exploration of multi-endpoint approaches promises insights into compound mechanisms of action, detection of safety concerns, and contributions to evolving regulatory standards.